2015
DOI: 10.1097/md.0000000000001218
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cardiotrophin-1 as a Marker of Hypertension and Diabetes-Induced Target Organ Damage and Cardiovascular Risk

Abstract: The search for biomarkers of hypertension and diabetes-induced damage to multiple target organs is a priority. We analyzed the correlation between plasma cardiotrophin-1 (CT-1), a chemokine that participates in cardiovascular remodeling and organ fibrosis, and a wide range of parameters currently used to diagnose morphological and functional progressive injury in left ventricle, arteries, and kidneys of diabetic and hypertensive patients, in order to validate plasma levels of CT-1 as clinical biomarker.This is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 44 publications
1
30
1
3
Order By: Relevance
“…The increased CT‐1 expression observed after UUO is congruent with CT‐1 acting as an endogenous defence mechanism activated to repair or counteract tubular injury, providing a protective effect against renal damage and fibrosis. Congruently with this, we previously reported that plasma levels of CT‐1 correlate with early renal damage (ie as evidenced by microalbuminuria and elevated albumin/creatinine ratio) in hypertensive and diabetic patients . All in all, these findings propose CT‐1 as a protective tissue barrier, as a potential biomarker of renal repair and, by extension, as a surrogate marker of renal fibrosis.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The increased CT‐1 expression observed after UUO is congruent with CT‐1 acting as an endogenous defence mechanism activated to repair or counteract tubular injury, providing a protective effect against renal damage and fibrosis. Congruently with this, we previously reported that plasma levels of CT‐1 correlate with early renal damage (ie as evidenced by microalbuminuria and elevated albumin/creatinine ratio) in hypertensive and diabetic patients . All in all, these findings propose CT‐1 as a protective tissue barrier, as a potential biomarker of renal repair and, by extension, as a surrogate marker of renal fibrosis.…”
Section: Discussionsupporting
confidence: 61%
“…Congruently with this, we previously reported that plasma levels of CT-1 correlate with early renal damage (ie as evidenced by microalbuminuria and elevated albumin/creatinine ratio) in hypertensive and diabetic patients. 38 All in all, these findings propose CT-1 as a protective tissue barrier, as a potential biomarker of renal repair and, by extension, as a surrogate marker of renal fibrosis.…”
Section: Discussionmentioning
confidence: 89%
“…In a study done by Gkaliagkousi et al [78], CT-1 levels was positively correlated with blood pressure and the indices of arterial stiffness. In another study, positive correlation between plasma CT-1 and basal glycemia, SBP and DBP were reported [79]. Also, they observed a positive association between CT-1 and arterial damage (increase intima-media thickness).…”
Section: Discussionmentioning
confidence: 89%
“…The present study complemented a growing list of candidate biomarkers for DCM, such as NT‐proBNP, ANP, Cardiotrophin‐1, IGFBP‐7, and GRK2. Different from the elevated GRK2 expression, elevated NT‐proBNP and ANP levels suggest the advanced stage of cardiomyopathy, especially for heart failure; plasma cardiotrophin‐1 expression elevated in diabetes patients with cardiac hypertrophy and systolic dysfunction; and IGFBP‐7 expression was revealed to be related to insulin resistant, cardiac hypertrophy, and cardiac fibrosis . These biomarkers represent several putative mechanistic pathways underlying DCM progression.…”
Section: Discussionmentioning
confidence: 99%